Status and Trends in Financial Inclusion and Financial Stability: A Comparative Analysis of SAARC Countries - B M Sajjad Hossain; Nasrin Akhter; Md. Taufiqul Islam; Md. Abul Hasam (Britain International for Academic Research (BIAR) Publisher, 2022)
Financial Inclusion (FI) refers to the process of bringing more people under the coverage of formal financial sector/s. It is very common in developed countries over the decades. But with the development of science and technology, financial inclusion has been introduced and spread in many developing nations in recent times. Most of the South Asian Association for Regional Cooperation (SAARC) nations are still under the category of developing economies. Mostly financial inclusion has taken part in this region for the last two decades. This research conducted a comparative study among the different SAARC nations based on the achievement in financial inclusion. This paper attempted to identify the sequential position of those countries as they can evaluate them by comparing each other for further improvement and stability.